Analgesic Effect of Passive Range-of-Motion Exercise on the Healthy Side for Pain after Total Knee Arthroplasty: A Prospective Randomized Trial - Shuichi Eto; Motoki Sonohata; Yasuo Takei; Masaya Ueno; Norio Fukumori; Masaaki Mawatari (Pain Research and Management)
Background. Exercise can reduce the pain threshold momentarily and induce analgesia, which is called exercise-induced hypoalgesia (EIH). Exercise therapy for inducing EIH may be an effective treatment option for pain. We aimed at investigating whether continuous passive motion (CPM) on both healthy and affected sides could induce EIH and reduce pain in the operated knee in patients after unilateral total knee arthroplasty (TKA). Patients and Methods. In this prospective randomized controlled trial, participants were randomly assigned to two groups: a bilateral group that received bilateral exercise on the operated and healthy sides and a unilateral group that received exercise therapy only on the affected side. We enrolled 40 patients aged ≥60 years who were scheduled to undergo unilateral TKA. Visual analogue scale (VAS) scores and range of motion (ROM) on the operated side were measured immediately before and after CPM on postoperative days 2, 4, 7, and 14. The primary outcome was the difference in the VAS scores before and after CPM on postoperative day 14. The secondary outcome was the difference in the ROM before and after CPM on postoperative day 14. Results. Comparison of VAS scores before and after CPM showed no significant intergroup differences on all measurement dates. However, there was a significant difference in values on day 14 (P<0.05). Both groups showed an increase in ROM after CPM, with significant increments observed on days 2 and 4 in the bilateral group and on day 14 in the unilateral group. There was no significant difference in values on postoperative day 14. Conclusion. Post-TKA pain was reduced by performing the same exercise on the healthy knee during CPM therapy. This could be due to EIH, and the results indicated that EIH can also influence postoperative pain immediately after surgery.